Zymography of proteases in honey bees (Apis Mellifera) infected with Nosema ceranae - Doghuzlu Mohammad Afrasiabi; Nabian Sedigheh; Paghaleh Gholam Ali Nehzati; Taheri Mohammad; Asadollahi Zahra; Akhzari Soheila (Veterinarski Glasnik)
Nosemosis is one of the most important honey bee diseases and is caused by two fungal species of the genus Nosema, i.e., Nosema apis and Nosema ceranae. Evidence suggests that in the coming years, Nosema ceranae, which is less sensitive to fumagillin, could replace Nosema apis as the predominant pathogenic Nosema. Identifying and developing drugs that target these microsporidia without having serious effects on host bee physiology is essential for controlling nosemosis, and this requires information about bee enzymes. Serine proteases, the major protease enzymes in insects, play an important role in the insect immune system. In the present study, some proteases of honey bees infected with N. ceranae were studied by zymography. PCR tests showed that all honey bee samples were infected with N. ceranae. Also, the protein pattern of infected honey bee tissue extracts was determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Bands with molecular weights of 25, 35, 48, 63, 75, and 100 kDa were observed. Subsequently, the serine proteases in the bees’ digestive tracts ranged in molecular weight between 23-35 kDa, and the molecular weight of cathepsins was 25 kDa by gelatin zymography. Investigation of bee proteases might be useful for acquiring more knowledge about the interaction between host and parasite and to access an effective and low-risk compound for nosemosis treatment.